Study on Spinning Forming Method of Cylindrical Parts with Quadrilateral Fillet Section - Yuliang Liu; Litong Zhang; Baichao Wang; Xin Wang (Jixie chuandong)
Based on the motion principle of guide bar mechanism，a spinning forming method of cylindrical parts with quadrilateral fillet section is proposed. Based on this principle and using the transformation method of high pair and low generation，the accurate mathematical model of the spinning wheel motion track in the spinning process of the cylinder with four corner fillet section is established，and the mechanism motion relationship of the spinning wheel and the parts is obtained. At the same time，the movement track of the spinning wheel in the forming process is simulated and calculated，and the influence of the spinning wheel number and wheel size on the spinning forming process is analyzed，and the wheel size and the number of the spinning wheel in the forming process which are conducive to the forming quality of the parts and improve the speed fluctuation of the wheel disc are obtained，which provides a theoretical basis for the research on the processing technology of the quadrilateral fillet shaped cylindrical parts.